Cognitive aspects of fetal alcohol spectrum disorder. Issue 1 (4th October 2012) - Davis, Krista M.; Gagnier, Karina Royer; Moore, Timothy E.; Todorow, Michelle
Abstract Nearly four decades have passed since a link was first established between alcohol consumption during pregnancy and a particular pattern of birth defects. Since then, autopsy, longitudinal, structural imaging, and functional imaging studies have revealed a great deal about the teratogenic effects of alcohol. This paper provides a comprehensive summary of the findings from the neurocognitive and behavioral literature on fetal alcohol spectrum disorder (FASD) and outlines the unique profile of cognitive deficits associated with it. We describe diagnostic issues as well as factors contributing to the heterogeneity of the FASD cognitive presentation. Next, we review research on the impact of prenatal alcohol exposure on intellectual functioning, attention, executive functioning, learning and memory, language, quantitative reasoning, and social cognition. In our opinion, future research can now begin to focus on FASD‐specific interventions directly informed by the rich body of neurocognitive findings accumulated thus far. WIREs Cogn Sci 2013, 4:81–92. doi: 10.1002/wcs.1202 For further resources related to this article, please visit the WIREs website.